PERBEDAAN KUALITAS PELAYANAN PASIEN RAWAT JALAN BPJS DENGAN PASIEN UMUM DI RUMAHSAKIT JIWA SAMBANG LIHUM - Paramitha, Rezky; Maulidie Alfiannor Saputera, Mochammad; Alexxander (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Pharmaceutical services are a crucial component in determining patient satisfaction levels at Sambang Lihum Psychiatric Hospital. This study aims to analyze differences in perceived service quality between outpatient participants of the Social Security Administration Agency (BPJS) and general (non-BPJS) patients. The research employed a cross-sectional design with an accidental sampling technique based on predetermined criteria, involving a total sample of 279 BPJS patients and 61 general patients. Data were analyzed using the Mann-Whitney test. The results showed a significant value (p = 0.002 < 0.05), indicating a meaningful difference in service quality between BPJS and general outpatient groups.